Microbreweries Communication Strategies: The Influence of Digital Media on Craft Beer Consumers in Mexicali, Baja California, Mexico - Espinoza Córdova, Jorge Luis; Bernardino López, Sergio; Córdova Ruíz, Zulema (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To evaluate the communication strategies of 7 craft breweries in Mexicali, Baja California; Mexico, which are based on the use and promotion on social networks, emails, web pages, or audiovisual content platforms.MATERIAL AND METHOD: Through a survey, the perception of its clients was measured and examined through an exploratory factor analysis to extract the factors that make it up, corroborate the independence between them and explain the greatest amount of variance.RESULTS: Three factors were formed that make up the communication strategy of microbreweries: development of loyalty, proximity to the consumer and presence on social networks. These describe the presence, frequency of use of digital media and the reach of the brand through interaction with craft beer consumers.CONCLUSIONS: It is highlighted that there is little proximity to the consumer in digital media and companies do not have a defined communication strategy and use the various media interchangeably, without knowing the reach of each one.
Keywords: Social networks; Digital marketing; Advertising strategies; Craft breweries.